Energy Intake and Total Daily Energy Expenditure Assessed by Subjective and Objective Methods in Older Individuals from a Tropical Setting in Brazil. (29th May 2020) - Anjos, Luiz Dos; Silva, Bruna; Wahrlich, Vivian
Abstract: Objectives: To assess different methods of estimating energy balance (EB) and its components in a sample of older people (age ≥ 60 years) living in a tropical city in Brazil. Methods: EB was calculated in 85 older individuals (69 women) as the difference between energy intake (EI), obtained by three 24-hour dietary recalls on nonconsecutive days, and total daily energy expenditure (TDEE) estimated by 24-hour physical activity recalls (24hPAR, subjective method) and accelerometry (ACC, objective method) on the same days. Basal metabolic rate (BMR) was estimated by a validated local predictive equations derived from a sample of healthy adults from the same city and by international equations (Schofield). Resting energy expenditure (MET) was also estimated by local predictive equation and the conventional value of 3.5 mL.kg −1 .min −1 . Anthropometry and % body fat (DXA) assessment was also obtained. Results: Mean (SD) age was 69.0 (5.5) years with a mean BMI of 26.7 (4.4) kg.m −2 and %BF of 39.4 (7.9). BMR from locally-derived equations (1050.7 ± 188.7 kcal.day −1 ) was significantly lower than BMR estimated by the Schofield's equation (1286.5 ± 145.3 kcal.day −1 ). Likewise, predicted MET was significantly lower than the conventional value. Despite the high prevalence of overweight (66% with BMI ≥ 25 kg.m −2 ), EB was always negative for the 24hPAR method (−863.5 ± 799.5 kcal.day −1 ) but positive (252.1 ± 726.6 kcal.day −1 ) with the ACC method when MET was calculated with population-specific equations. EB estimated by ACC was also negative (−122.7 ± 781.0 kcal.day −1 ) using the conventional MET value. Conclusions: The findings of this study indicate that EB is negative when the subjective method of TDEE estimation is used but becomes positive with the objective method. It is also evident that BMR and MET equations derived from samples of the population of interest may help improve the final estimates of TDEE and EB in older adults. Funding Sources: CNPq (310, 461/2016–20 and 485, 168/2011–1) and FAPERJ (E-26/111.496/2011; E-26/202.514/2018; E-26/203.068/2017).